2021
DOI: 10.3389/fimmu.2021.654259
|View full text |Cite
|
Sign up to set email alerts
|

Released Myeloperoxidase Attenuates Neutrophil Migration and Accumulation in Inflamed Tissue

Abstract: Neutrophil (PMN) recruitment to sites of insult is critical for host defense, however excessive PMN activity and tissue accumulation can lead to exacerbated inflammation and injury. Myeloperoxidase (MPO) is a PMN azurophilic granule enzyme, which together with H2O2, forms a powerful antimicrobial system designed to kill ingested bacteria. Intriguingly, in addition to intracellular killing of invading microorganisms and extracellular tissue damage due generation of ROS, soluble MPO has been directly implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…21 In addition, the MPO activity served as a reliable marker of the neutrophil activation and high levels of MPO indicate increased inflammation. 22 The present study indicated that the GSPE treatment could suppress the alterations of the increased MPO activities, the increased MDA contents, and the reduced GSH-Px activities, consistent with the research results of the previous studies, 23,24 and the antioxidant capacity of high-dose GSPE was higher than that of low-dose GSPE. Therefore, the findings summarized above established the antioxidant potential capacity of GSPE.…”
Section: Discussionsupporting
confidence: 92%
“…21 In addition, the MPO activity served as a reliable marker of the neutrophil activation and high levels of MPO indicate increased inflammation. 22 The present study indicated that the GSPE treatment could suppress the alterations of the increased MPO activities, the increased MDA contents, and the reduced GSH-Px activities, consistent with the research results of the previous studies, 23,24 and the antioxidant capacity of high-dose GSPE was higher than that of low-dose GSPE. Therefore, the findings summarized above established the antioxidant potential capacity of GSPE.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, neutrophils treated with stimuli are rich in MPO-DNA complexes ( 38 ) and, in turn, MPO can regulate the function and immune response of neutrophils. Recent research has shown that MPO can affect the degranulation of neutrophils and improve their phagocytosis ( 39 ), and it can also “break” the migration of neutrophils and prevent their accumulation ( 15 ). The relationship between MPO in CRC and preoperative neutrophil counts is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Given the controversial effect of MPO on CRC, there has been growing interest in investigating the role of this enzyme in CRC. MPO is the most abundant protein expressed by neutrophils and it may also have the greatest potential to damage living cells ( 15 ). In autoimmune diseases, MPO exists only in the cytoplasm of the neutrophils ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is information that MPO is held responsible in the pathogenesis of many inflammatory diseases, including cardiovascular, kidney, lung, rheumatoid arthritis, skin inflammation and neuronal 23 . The damaging effect of MPO on tissue is enhanced by the formation of hypochlorous acid from hydrogen peroxide and chloride ions 24 . The inhibition of MPO activity by acrylamide by HRE may be due to its inhibition of PNL leakage (infiltration) into the damaged area.…”
Section: Discussionmentioning
confidence: 99%